Need Analysis to Create a Better Instruction and Material for ESP Management Students - Dwita Laksmita Rachmawati; Sri Hastari; Joes Dwiharto (Universitas Muhammadiyah Mataram, 2021)
It is pivotal for English for Specific Purposes (ESP) teachers to conduct need analysis before they start to teach ESP students. It is required to portray the needs of the ESP students to learn English to fit with their real life. That is why ESP teachers have to be able to support the student with a fit module, instructions, and many other aspects for the effectiveness and the success of ESP course. This study aims to discover what the students need to gain after learning English and what environment and learning materials can boost their motivation to learn English. This research used quantitative research method in which the researchers administer a questionnaire to the participants of the study. The questionnaire consisted of two categorizes, namely Learning Need Analysis (LNA) and Target Situation Analysis (TSA) that is adapted and modified from (Hutchinson, T. & Waters, 1987). The respondents of the study were 66 first-year students of the Management program. The findings divide into 6 parts. There were students' (1) Goal (2) Competence (3) Problem (4) Expectation (5) Preferred learning activities (6) Preferred classroom setting. The results need to be considered to improve the students’ learning environment and receive proper material designated for their major. It can also enhance their awareness of the importance of English for their future career as they still lack motivation.